Constructing social meaning in political discourse: Phonetic variation and verb processes in Ed Miliband's speeches. (17th November 2015) - Kirkham, Sam; Moore, Emma
Abstract: This article investigates how variation across different levels of linguistic structure indexes ideological alignments in political talk. We analyse two political speeches by Ed Miliband, the former leader of the UK Labour Party, with a focus on the use of /t/-glottalling and the types of verb processes that co-occur with the pronouns we and you . We find substantial differences in the production of /t/ between the two speeches in words such as Britain and government, which have been argued to take on particular salience in British political discourse. We contextualise these findings in terms of metalinguistic discourse surrounding Miliband's language use, as well as how he positions himself in relation to different audiences via verb process types. We show that phonetic variation, subject types, and verb processes work synergistically in allowing Miliband to establish a political persona that is sensitive to ideological differences between different audiences. (Social meaning, indexicality, political discourse, verb processes, phonetic variation, /t/-glottalling)*